The importance of nursing in education on living organ donation: Integrative Systematic Review (Research, Society and Development, 2023)
Introduction: This work constitutes a study on living organ donation and its significance as the primary option for treating various diseases. Currently, over 60,000 individuals await organ transplantation in the country, with more than 37,000 awaiting a kidney. Objectives: To elucidate the process of living organ transplantation, understand the primary forms of organ and tissue donation, and explore Nursing's contribution in this process. Methodology: This is an Integrative Systematic Review of scientific articles addressing Nursing's role in educating about living organ donation. The PICO strategy guided this study's objectives, yielding 640 bibliographic returns, with only 73 articles selected for analysis. Conclusions: This study underscores the importance of living organ donation due to the scarcity of awareness regarding its potential to save lives and alleviate organ shortages. Addressing ethical and legal considerations, the text highlights the complexity of the subject. The research, employing the Integrative Systematic Review method, reveals gaps in public understanding, emphasizing the necessity for accurate and comprehensive information. The nurse's role in patient education and support is emphasized. Further investigation into the donation process is suggested, alongside the promotion of precise information through hospital and family health settings via lectures and educational sessions.